PROPOSAL OF ACTIONS FOR THE PROMOTION OF SUSTAINABLE DEVELOPMENT FROM THE PREPARATION OF SPORTS TEACHERS IN ORDER TO APPLY THE “LIFE TASK” TO SCHOOL SPORTS INITIATION - Ochoa Hernández, Jennifel (2023)
The research presented is aimed at the methodological preparation of the teachers of the Sports Combine No. 2. “Mártires de Jatibonico”, located in the municipality of Sancti Spíritus, in the Jatibonico municipality, to integrate the three dimensions of sustainable development into the classes of School Sports Initiation to promote developmental learning in students, and a process of awareness of the environment, towards more sustainable forms of construction of a subject socially committed to the environment. Therefore, the objective of this work is to propose awareness-raising actions that enhance teaching and learning to generate a sustainable-environmental approach in the school sports initiation classes, and thereby demonstrate the nature of the science and technology process, to prepare boys and girls to integrate, analyze and understand, through sensitive observation, the habitat that surrounds them. These actions incorporate the dimensions of sustainable development into the contemporary classroom to achieve problematizing and meaningful learning.